2001
DOI: 10.1074/jbc.m008118200
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic Deletion of Three Intracellular Acidic Residues of the α2B-Adrenergic Receptor Decreases G Protein-coupled Receptor Kinase-mediated Phosphorylation and Desensitization

Abstract: A polymorphic variant of the human ␣ 2B -adrenergic receptor (␣ 2B AR), which consists of a deletion of three glutamic acids (residues 301-303) in the third intracellular loop was found to be common in Caucasians (31%) and to a lesser extent in African-Americans (12%). The consequences of this deletion were assessed by expressing wild-type and the Del301-303 receptors in Chinese hamster ovary and COS cells. Ligand binding was not affected, although a small decrease in coupling efficiency to the inhibition of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
129
1
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(143 citation statements)
references
References 30 publications
7
129
1
6
Order By: Relevance
“…28 Study using a in vitro cell culture model indicated that the Glu9 variant of the a 2B -AR resulted in a complete loss of the ability for the receptor to undergo agonist-promoted phosphorylation compared with the Glu12 variant. 5 Our findings extend the knowledge to the alteration of the cardiac sympathetic and vagal functions during sustained handgrip exercise in humans with 12Glu9 deletion polymorphism of the a 2B -AR gene. In fact, the present study provides evidences that normotensive women with Glu 9 /Glu 9 genotype have attenuated increase in sympathetic modulation and attenuated reduction in parasympathetic modulation during sustained handgrip exercise when compared with Glu 12 /Glu 12 and Glu 12 /Glu 9 genotypes.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…28 Study using a in vitro cell culture model indicated that the Glu9 variant of the a 2B -AR resulted in a complete loss of the ability for the receptor to undergo agonist-promoted phosphorylation compared with the Glu12 variant. 5 Our findings extend the knowledge to the alteration of the cardiac sympathetic and vagal functions during sustained handgrip exercise in humans with 12Glu9 deletion polymorphism of the a 2B -AR gene. In fact, the present study provides evidences that normotensive women with Glu 9 /Glu 9 genotype have attenuated increase in sympathetic modulation and attenuated reduction in parasympathetic modulation during sustained handgrip exercise when compared with Glu 12 /Glu 12 and Glu 12 /Glu 9 genotypes.…”
Section: Discussionsupporting
confidence: 73%
“…[1][2][3][4] The functional significance of the 12Glu9 polymorphism of the a 2B -AR gene investigated in vitro cell culture model indicated that the Glu9 variant was associated with impaired receptor desensitization properties under prolonged agonist activation as compared with the Glu12 variant. 5 Studies in obese humans demonstrated that the homozygote short form of a 2B alleles (Glu 9 /Glu 9 ) were associated with slower heart rate (HR). 1 And, a 10-year follow-up study showed that the decrease in parasympathetic function in nondiabetic men with abdominal obesity and impaired cardiac autonomic nervous system (ANS) modulation who were homozygous for Glu 9 /Glu 9 a 2B -AR was greater than the other genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Five SNPs (Ϫ2014, Ϫ1903, Ϫ1607, 753, and 849) were found exclusively in African Americans, although the allele frequency of the latter was only 0.01. Compared with the ␤ 1 AR (25,26), ␤ 2 AR (27, 28), ␣ 2B AR (29), and ␣ 2C AR (30), which have high-frequency nonsynonymous polymorphisms, the current data show that the ORF of the ␣ 2A AR is virtually invariant at the encoded protein level except for the uncommon substitution at 753, which was found only in those of African descent.…”
Section: Resultsmentioning
confidence: 83%
“…The increased amygdala response we observed in deletion carriers as compared with nondeletion carriers may result from changes in noradrenaline availability, because the deletion leads to a perturbation of the relationship between incoming noradrenaline signals and receptor responsiveness (23). The α2b-adrenoreceptor is a presynaptic receptor and has a negative feedback function.…”
Section: Discussionmentioning
confidence: 93%
“…In vitro data suggest that the deletion exerts both agonistic and antagonistic effects (23). This deletion has been found to be associated with increased reexperiencing of traumatic memories in humans (24), which suggests that the deletion acts as a reduced-function variant.…”
mentioning
confidence: 99%